2021
DOI: 10.3390/healthcare9121730
|View full text |Cite
|
Sign up to set email alerts
|

Development of Serological Assays and Seroprevalence Studies of the New Coronavirus 2019 (COVID-19): Reports from Saudi Arabia

Abstract: Serological assays are valuable tools for tracking COVID-19 spread, estimation of herd immunity, and evaluation of vaccine effectiveness. Several reports from Saudi Arabia describe optimized in-house protocols that enable detection of SARS-CoV-2 specific antibodies and measurement of their neutralizing activity. Notably, there were variations in the approaches utilized to develop and validate these immunoassays in term of sample size, validation methodologies, and statistical analyses. The developed enzyme-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…[24][25][26][27][28] It is also vital to note that SNT in many instances, ). 31,[37][38][39][40] We also found 11 recovered cases (6 with normal BMI and 5 with various degree of obesity) with confirmed PCR diagnosis tested negative for IgG NP-ELISA which supports previous studies that reported antibody waning following recovery. 37,41,42 These results demonstrate the potential vulnerability of recovered patients to reinfection and highlight the importance of vaccination uptake for this population.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…[24][25][26][27][28] It is also vital to note that SNT in many instances, ). 31,[37][38][39][40] We also found 11 recovered cases (6 with normal BMI and 5 with various degree of obesity) with confirmed PCR diagnosis tested negative for IgG NP-ELISA which supports previous studies that reported antibody waning following recovery. 37,41,42 These results demonstrate the potential vulnerability of recovered patients to reinfection and highlight the importance of vaccination uptake for this population.…”
Section: Discussionsupporting
confidence: 89%
“…Since the pandemic started, many studies reported asymptomatic cases with lack of self‐awareness which probably increased due to the emergence of variants with high transmissibility and mild pathogenicity (e.g., Omicron; B.1.1.529). 31 , 37 , 38 , 39 , 40 We also found 11 recovered cases (6 with normal BMI and 5 with various degree of obesity) with confirmed PCR diagnosis tested negative for IgG NP‐ELISA which supports previous studies that reported antibody waning following recovery. 37 , 41 , 42 These results demonstrate the potential vulnerability of recovered patients to reinfection and highlight the importance of vaccination uptake for this population.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Iron deficiency (ID) is a global health problem that affects nearly two billion people [ 1 ], and iron deficiency anemia (IDA) is considered the topmost leading cause of anemia worldwide [ 2 ]. The prevalence of ID and IDA is generally higher in women of child-bearing age, preschool children, and individuals with low socioeconomic status [ 1 , 3 ]. The underdeveloped regions have a five-time higher prevalence rates of ID and IDA compared to the developed nations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%